Epidemiological and clinical characteristics analysis of COVID-19 in the surrounding areas of Wuhan, Hubei Province in 2020. (July 2020) - Zheng, Yi; Xiong, Chang; Liu, Yuquan; Qian, Xin; Tang, Yijun; Liu, Liang; Leung, Elaine Lai-Han; Wang, Meifang
Graphical abstract: Abstract: Aim: Since December 2019, new COVID-19 outbreaks have occurred and spread around the world. However, the clinical characteristics of patients in other areas around Wuhan, Hubei Province are still unclear. In this study, we performed epidemiological and clinical characteristics analysis on these regional cases. Methods: We retrospectively investigated COVID-19 patients positively confirmed by nucleic acid Q-PCR at Taihe Hospital from January 16 to February 4, 2020. Their epidemiological, clinical manifestations, and imaging characteristics were analysed. Results: Among the 73 patients studied, 12.3 % developed symptoms after returning to Shiyan from Wuhan, and 71.2 % had a history of close contact with Wuhan personnel or confirmed cases. Among these patients, 9 cases were associated with family clustering. The first main symptoms presented by these patients were fever (84.9 %) and cough (21.9 %). The longest incubation period was 26 days, and the median interval from the first symptoms to admission was 5 days. Of the patients, 67.1 % were originally healthy people with no underlying diseases, others mostly had common comorbidities including hypertension (12.3 %) and diabetes (5.5 %), 10.9 % were current smokers, 30.1 % had low white blood cell counts and 45.2 % showed decreased lymphocytes at the first time of diagnosis. CT scans showed that multiple patchy ground glass shadows outside of the patient lungs were commonly observed, and a single sub-pleural sheet of ground glass shadow with enhanced vascular bundles was also found located under the pleura. Patient follow-up to February 14 presented 38.4 % severe cases and 2.7 % critical cases. After follow-up, the parameter of lymphocyte counts below 0.8 × 10 9 /L cannot be used to predict severe and critical groups from the ordinary group, and a lower proportion of smokers and higher proportion of diabetes patients occur in the poor outcome group. Other co-morbidities are observed but did not lead to poor outcomes. Conclusion: The epidemiological characteristics of patients in the area around Wuhan, such as Shiyan, at first diagnosis are described as follows: Patients had histories of Wuhan residences in the early stage and family clustering in the later period. The incubation period was relatively long, and the incidence was relatively hidden, but the virulence was relatively low. The initial diagnosis of the patients was mostly ordinary, and the percentage of critical patients who evolved into the ICU during follow-up is 2.7 %, which is lower than the 26.1 % reported by Wuhan city. According to the Shiyan experience, early diagnosis with multiple swaps of the Q-PCR test and timely treatment can reduce the death rate. Diabetes could be one of the risk factors for progression to severe/critical outcomes. No evidence exists that smoking protects COVID-19 patients from developing to severe/critical cases, and the absolute number of lymphocytes at initial diagnosis could not predict the progression risk from severe to critical condition. Multivariate regression analysis should be used to further guide the allocation of clinical resources.